Geographical Classification and Adulteration Detection of Cumin by Using Electronic Sensing Coupled to Multivariate Analysis. (2017) - Tahri, Khalid; Tiebe, Carlo; Bari, Nezha El; Hübert, Thomas; Bouchikhi, Benachir
Abstract: The objective of this work is to report the improvement obtained in the discrimination of complex aroma and taste with subtle differences in odor and flavor, by the use of fast suitable procedures for the cases of measurements in the field demanding decision-making in real time. The proposed electronic sensing systems, formed by an E-nose and VE-tongue, were used to discriminate cumin cultivars from different geographical origins, as well as to quantify the cumin adulteration percentages by using unsupervised and supervised chemometric tools. Thus, the results obtained are sufficiently encouraging as a starting point for the development of new electronic sensing systems with more improvement such the reliability of the sensors' performance as well as the chemometric tools in order to deal with a complex dataset.